Backchannel behavior is idiosyncratic - Peter Blomsma; Julija Vaitonyté; Gabriel Skantze; Marc Swerts (Language and Cognition)
In spoken conversations, speakers and their addressees constantly seek and provide different forms of audiovisual feedback, also known as backchannels, which include nodding, vocalizations and facial expressions. It has previously been shown that addressees backchannel at specific points during an interaction, namely after a speaker provided a cue to elicit feedback from the addressee. However, addressees may differ in the frequency and type of feedback that they provide, and likewise, speakers may vary the type of cues they generate to signal the backchannel opportunity points (BOPs). Research on the extent to which backchanneling is idiosyncratic is scant. In this article, we quantify and analyze the variability in feedback behavior of 14 addressees who all interacted with the same speaker stimulus. We conducted this research by means of a previously developed experimental paradigm that generates spontaneous interactions in a controlled manner. Our results show that (1) backchanneling behavior varies between listeners (some addressees are more active than others) and (2) backchanneling behavior varies between BOPs (some points trigger more responses than others). We discuss the relevance of these results for models of human–human and human–machine interactions.